Application and Significance of the Sadharanikaran Model of Communication (SMC) in Foreign Language Pedagogy - Su, Zhengju (Bodhi: An Interdisciplinary Journal, 2024)
This paper examines the Sadharanikaran Model of Communication (SMC) and its application in foreign language pedagogy. Rooted in Indian philosophy, SMC offers a holistic view of communication, emphasizing the interplay between the communicator, message, and recipient. It posits that communication is influenced by cultural and social contexts, which can enhance language teaching by promoting a learner-centered approach. By integrating SMC principles into language curricula, teaching materials, and classroom activities, educators can foster a deeper understanding of communication processes and adapt their methodologies accordingly. The study highlights the benefits of using authentic materials and creating inclusive learning environments to improve language acquisition and cross-cultural understanding among students. It explores how SMC principles can facilitate language learning as a dynamic and interactive process, encouraging educators to adopt strategies that value the unique experiences and perspectives of each student. By promoting cultural empathy and intercultural sensitivity, SMC provides a framework for cultivating communicative competence and enhancing the overall effectiveness of foreign language education.